2020
DOI: 10.1002/lary.29162
|View full text |Cite
|
Sign up to set email alerts
|

Neuromodulators for Atypical Facial Pain and Neuralgias: A Systematic Review and Meta‐Analysis

Abstract: Objective: To evaluate the effectiveness of neuromodulating agents for the management of atypical facial pain and primary facial neuralgias.Methods: We searched MEDLINE, Embase, CINAHL, and ClinicalTrials.gov databases for original research articles that examine the effectiveness and adverse reactions of pharmacologic therapy for the treatment of trigeminal neuralgia and atypical facial pain. Studies that included surgical interventions for atypical facial pain or facial pain secondary to other causes were exc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 67 publications
(346 reference statements)
0
16
0
Order By: Relevance
“…Although BoNT has been suggested as an effective treatment to counter neuropathic pain [ 29 , 30 , 31 , 32 , 33 , 34 , 35 ], evidence in the literature is mainly focused on the unidimensional evaluation of pain, with different systematic reviews assessing the Visual Analogue Scale (VAS) or Numerical Rating Scale (NRS). Conversely, given the psychosocial and functional burden of neuropathic pain, a multidimensional assessment of this condition is needed, in order to promote a patient-centered approach.…”
Section: Introductionmentioning
confidence: 99%
“…Although BoNT has been suggested as an effective treatment to counter neuropathic pain [ 29 , 30 , 31 , 32 , 33 , 34 , 35 ], evidence in the literature is mainly focused on the unidimensional evaluation of pain, with different systematic reviews assessing the Visual Analogue Scale (VAS) or Numerical Rating Scale (NRS). Conversely, given the psychosocial and functional burden of neuropathic pain, a multidimensional assessment of this condition is needed, in order to promote a patient-centered approach.…”
Section: Introductionmentioning
confidence: 99%
“…In 2011, Martin et al [ 38 ] reviewed the results of the study by Campbell et al [ 7 ] and found that pain intensity was reduced by 58% in the carbamazepine group compared with 26% in the placebo group. In their meta-analyses, Do et al [ 22 ] found that carbamazepine had a clinically significant pain reduction in patients with TN; however, they also found that patients had hematologic side effects and recommended further studies on new anticonvulsants such as oxcarbazepine. Six reviews of the literature agree that carbamazepine should be a first-line drug therapy for TN, but should be used with caution due to side effects [ 39 40 41 42 43 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Botulinum toxin has also been systematically reviewed for its effectiveness in the treatment of TN [ 21 22 ]. Although not within the scope of this review, it is currently under consideration as a treatment modality[ 22 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other anticonvulsants, including gabapentin, pregabalin, lamotrigine, and topiramate, have also been used as a monotherapy or in combination with carbamazepine or oxcarbazepine, although there is only low quality evidence supporting their use [20]. In addition, botulinum toxin A, an inhibitor of acetylcholine release at the neuromuscular junction, has been reported to reduce pain symptoms [124]. Despite the variety of available treatment options, relieving pain in patients with PTN has been unsatisfactory, with large inter-patient variability [61].…”
Section: Efficacy Of Clinically Used Drugsmentioning
confidence: 99%